Entry phase in men`s backward dive pike: association between the shoulder joint and trunk angles - Narita, T.; Okubo, Y.; Nomura, T.; Kaneoka, K. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: A high prevalence of lower back pain has been observed in competitive divers. Hyperextension of the lumbar vertebrae during water entry is considered the main mechanism behind the incidence of lower back pain in divers. Therefore, this study aimed to investigate the influence of the shoulder angle on the entry alignment. METHODS: Posture angles of 13 male drivers (age: 16.8±2.9 years) who were invited to the national training camp in 2012 by Japan Swimming were recorded at the time of water entry via 201B using a high-speed camera. RESULTS: A negative correlation was observed between shoulder joint flexion and trunk extension angles on water entry. In addition, the trunk angle was significantly different between groups. For the lower back pain group, 210.4±5.7°, and in the non-lower back pain group, 199.9±9.0°, angles were observed with a larger extension of the trunk on water entry in the lower back pain group. CONCLUSIONS: The alignment on water entry was associated with the occurrence of lower back pain. Which suggested that enough shoulder flexibility can prevent the incidence of lower back pain.